Dia:Beacon - Cooke, Lynne; Govan, Michael; Frankel, David; Schröder, Barbara; Dia:Beacon, New York (New York : Dia Art Foundation, 2003)
Becher, Hilla ; Becher, Bernd ; Beuys, Joseph ; Bourgeois, Louise ; Chamberlain, John ; Darboven, Hanne ; De Maria, Walter ; Flavin, Dan ; Heizer, Michael ; Irwin, Robert ; Judd, Donald ; Kawara, On ; Knoebel, Imi ; LeWitt, Sol ; et al.
Published to celebrate the opening of Dia:Beacon in New York, a museum of Dia Art Foundation
kunstcatalogus